2009
DOI: 10.1186/cc7918
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and adverse effect on outcome of hyperlactatemia in the critically ill

Abstract: IntroductionHyperlactatemia is frequent in critically ill patients and is often used as a marker of adverse outcome. However, studies to date have focused on selected intensive care unit (ICU) populations. We sought to determine the occurrence and relation of hyperlactatemia with ICU mortality in all patients admitted to four ICUs in a large regional critical care system.MethodsAll adults ([greater than or equal to] 18 years) admitted to ICUs in the Calgary Health Region (population 1.2 million) during 2003 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
119
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(130 citation statements)
references
References 26 publications
9
119
1
1
Order By: Relevance
“…Similarly, lactatemia on admission to the ICU is a well-known prognostic and severity marker. 33,34 In the early postoperative period after LT, these factors could also be considered surrogate markers of inflammation or prothrombotic disorders induced by the surgery and liver graft function. The duration of postoperative mechanical ventilation after LT could also be related to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, lactatemia on admission to the ICU is a well-known prognostic and severity marker. 33,34 In the early postoperative period after LT, these factors could also be considered surrogate markers of inflammation or prothrombotic disorders induced by the surgery and liver graft function. The duration of postoperative mechanical ventilation after LT could also be related to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…As a matter of fact, hyperlactatemia was firstly reported as a parameter for measurement of "reversibility" [16]. Then, in recent years, most reports show a prognostic value of hyperlactatemia on predicting mortality in both adults and children in lots of medical illnesses, including shock, sepsis, trauma, surgery and especially after cardiac interventions [17][18][19][20][21][22]. Although there are reports that admission hyperlactatemia predicts mortality and clinical outcome, the predictive value of a single lactate assessed on admission is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…On the study of Revelly et al (12) it is commented that patients with cardiogenic shock have a rise in lactate production, but are able to maintain its clearance, which differs from our study. Our sample is small; therefore it had not a statistical significance in the multivariate analysis (11)(12)(13)(14)(15)(16).…”
Section: Discussionmentioning
confidence: 99%
“…The best lactate clearance rate is correlated as well with decreased in some biomarker such as interleukins 1,6,8,10, tumor necrosis factor alpha, caspase 3. On the other hand, some studies have demonstrated that normal lactate rates can be found on cardiogenic shock, acute renal failure, and that lactate clearance are altered on these, probably because of multiorgan failure (9,(10)(11)(12)(13)(14)(15)(16). On the majority of studies performed, the effectiveness of lactate clearance determination are compared to predictors mortality scores such as APACHE II, SOFA, SAPS II, concluding that lactate clearance may be by itself a good mortality prognostic factor (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%